Cancer Therapy: Gold Nanoparticle‐Loaded Neural Stem Cells for Photothermal Ablation of Cancer (Adv. Healthcare Mater. 7/2013). Issue 7 (10th July 2013) - Schnarr, Kenna; Mooney, Rachael; Weng, Yiming; Zhao, Donghong; Garcia, Elizabeth; Armstrong, Brian; Annala, Alexander J.; Kim, Seung U.; Aboody, Karen S.; Berlin, Jacob M.
<x xml:space="preserve">Abstract</x> Neural stem cells carrying internalized gold nanorods home in on cancer. Stimulating the nanorods with a near infrared laser causes them to heat up and kill surrounding cancer cells. The laser alone is non‐harmful so cell killing only occurs where the stem cells have taken the nanorods. Further details can be found in the article by Jacob M. Berlin, Karen S. Aboody, and co‐workers on page 976. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>